Evidance Based Practice Bermain Puzzle dengan Demensia di Panti Werdha Damai Ranomuut - Kairupan, Michelle; Mokobimbing, Frensi (JURNAL ILMIAH KESEHATAN MANADO, 2025)
Dementia is a condition in which a person experiences a decrease in memory and thinking. This decline in ability causes disruption to the functioning of daily life. Dementia occurs due to cognitive impairment. One of the efforts that can be done to reduce cognitive function disorders is by providing puzzle play therapy. The purpose of this scientific paper is the implementation of nursing care with the application of evidence-based puzzle play therapy to improve cognitive function in Mrs. H. R at the peace orphanage ranomuut. The results of the study with the application of evidence-based puzzle play therapy which was carried out for 3 days, the results of the evaluation were found that puzzle play therapy was effective in improving cognitive function in Mrs. H. R from moderate cognitive aspect disorders 16 increased cognitive aspects with 26 results. Conclusion: This scientific paper showed an improvement in cognitive function in Mrs. H. R who experienced dementia after being given puzzle play therapy. Suggestion: to all health workers to be able to provide action and education in providing puzzle play therapy to clients suffering from dementia.